On the synthesis of N–O bearing species in astrophysical ices – an infrared spectroscopic study using heavy-ion irradiation of solid N2:CO samples. Issue 1 (22nd December 2021) - Bergantini, A; de Barros, A L F; Domaracka, A; Rothard, H; Boduch, P; da Silveira, E F
ABSTRACT: The interstellar chemistry of nitrogen is considerably less understood than the chemistry of other common elements, such as carbon and oxygen. Even though a relatively large number of species containing nitrogen atoms have already been detected in the interstellar medium, only six of them bear a nitrogen–oxygen (N–O) bond. Some astrophysical and primeval Earth models suggest that N–O species, such as hydroxylamine (NH2 OH), are potential precursors of prebiotic amino acids, and even peptides. In this work, we have analyzed an apolar ice mixture of N2 :CO of astrophysical interest to investigate possible formation mechanisms of N–O bearing molecules due to processing of the sample by 64 Ni 24+ 538 MeV ions (8.4 MeV/u) at 14 K. The results show the formation of simple nitrogen oxides (N_1 - 2O_y), but no CN–O species of any kind. We have also determined the formation cross-sections of some of the products, as well as the destruction cross-sections of precursors and products. The results presented here are discussed in light of our previous work on the processing of a NH3 :CO ice mixture, which have found no N–O bearing molecules at all.